In the community : an intermediate integrated skills textbook. - NorQuest College; BC Open Textbook Project; BCcampus (NorQuest College, 2016)
"This is an English-language skills textbook to help ESL students acquire communication skills in the community (listening, speaking, reading, and writing). The book is aimed at Canadian Language Benchmark (CLB) levels 5/6, focusing on intercultural skills and essential skills: reading text, document use, writing, oral communication, thinking skills, working with others, and computer use"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online version; Title from PDF (viewed on May 4, 2017).
Keywords: English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; Reading comprehension -- Problems, exercises, etc; Electronic books